Réponses

2012-12-07T19:49:32+01:00

1) 2x(9x²-3x+6x-2)=0

18x^3-6x²+12x²-4x=0

18x^3+6x²-4x=0

x(18x²-6x-4)

x=0

calcul du discriminant

delta= b²-4ac

delta=(-6)²-4*18*(-4)

delta=36+288

delta=324

x1=(-b- racine carré delta)/2a

x1=(6-18)/2*18

x1=-1/3

x2=(-b+racine carré delta)/2a

x2=(6+18)/2*18

x2=2/3

S={-1/3; 0; 2/3}

 

3)6(y+3)-2(y-1)=0

6y+18-2y+2=0

4y+20=0

4y=-20

y=-5

 

 

 

 

 

Meilleure réponse !
2012-12-07T22:38:52+01:00

Bonsoir

2x(3x+2)(3x-1) = 0 il suffit que l'un des facteurs soit nul 

2x = 0  soit x= 0

ou 3x+2 = 0  alors x = -2/3

ou 3x-1 = 0          x = 1/3 

 

6(y+3)-2(y-1) = 0 on développe 

6y + 18 - 2y +2 = 0 

4y +20 = 0 

4y = -20 

y = -20/4 = -5